KAJIAN DELIGNIFIKASI PULP FORMACELL DARI TANDAN KOSONG KELAPA SAWIT MENGGUNAKAN HIDROGEN PEROKSIDA (H2O2) DALAM MEDIA ASAM ASETAT - Zuidar, Ahmad Sapta; Hidayati, Sri; Pulungan, Rafma Junita Ariana (Jurnal Teknologi & Industri Hasil Pertanian, 2014)
The waste of palm oil industry that can be used as raw materials for pulp making industry is palm oil empty fruit bunches. The common method used in the pulp production process is Formacell. However, formacell process produced dark pulp because of high lignin content. Therefore it needs further process called delignification. This process utilized H2O2 in acetic acid media to improve pulp qualities. The aim of this research was to determine the effect of different concentrations of H2O2 in acetic acid media on the characteristics of pulp formacell from palm oil empty fruit bunches. The experiment was arranged in a Complete Randomized Block Design with a single treatment and 3 replications. The treatment was nine levels of H2O2 concentration ( 0%, 3%, 6%, 9%, 12%, 15%, 18%, 21%, 24%) in acetic acid media at a temperature of 85oC for 3 hours. The data homogenity and additivity were analyzed using Berlett and Tuckey Tests, then they were analyze for ANOVA to see any difference in the data and then tested further using Ortogonal Polinomial. The results showed that the concentration of H2O2 in acetic acid media had significant effect on yield, cellulose, hemicellulose, lignin, and color of pulp from palm-oil empty fruit bunches. The result of ortogonal polynomial test showed the increase in concentrations of H2O2 in acetic acid media linearly decreased yield and hemicellulose, linearly increased organoleptic color score, quadratically decreased lignin content , and quadratically increased cellulose until concentration 50% of H2O2 in15% acetic acid media, beyond that, the cellulose content decreased. The best results showed that 50% of H2O2 in 15% of acetic acid media cooked for 3 hours gave the best pulp. This pulp contained cellulose, hemicelluloses and lignin of 84.494% 6.319% and 5.691% . The yield was 84.85%, and the average organoleptic score for color was 4. Keywords: acetic acid, delignification, formacell pulp, H2O2, oil palm empty fruit bunches